Effects of residual stress patterns on TBC systems - EKİCİ, BÜLENT (MANEY PUBLISHING, 2004)
In recent studies, interfacial toughness in thermal barrier coating (TBC) systems was measured by indentation tests. The layers existing in the TBC systems were simplified to a system consisting of a coating and a substrate. The second simplification is that the residual stress values were taken as average values in the calculation. The types of residual stresses which may occur in TBC systems have not been studied. In the present paper, different residual stress patterns are applied to the model, and they are not taken as average values because some residual patterns are not scalar values but linear or parabolic functions. Results are presented for application in the measurement of the interfacial toughness of TBC systems using a simple indentation test simulation technique.
Keywords: residual stress; interfacial toughness; indentation; DUCTILE SUBSTRATE; INDENTATION; TOUGHNESS; ADHESION; DELAMINATION; ALLOYS; FILM